Staphylococcus aureus Bacteremia in Children: Antibiotic Resistance and Mortality. Issue 5 (May 2019) - Gordon, Oren; Cohen, Matan J.; Gross, Itai; Amit, Sharon; Averbuch, Dina; Engelhard, Dan; Milstone, Aaron M.; Moses, Allon E.
Abstract : Background: Staphylococcus aureus (SA) is a major cause of bacteremia in children. Methicillin-resistant SA (MRSA) is considered a public health threat; however, the differences in the prognosis of children with methicillin-susceptible SA (MSSA) versus MRSA bacteremia are not well defined. Methods: Data from all SA bacteremia events in children (0–16 years) from 2002 to 2016 in a single Israeli tertiary center were collected. Positive cultures within 48 hours of hospitalization were considered community associated (CA). Those obtained afterward or from children hospitalized within the previous year were considered health-care associated (HA). Results: We recorded 427 events, 284 (66%) were HA, 64 (15%) were MRSA and 9 (2%) were CA-MRSA. There was no increase in MRSA during the study period. In-hospital, 30-day and 1-year mortality were 3% (12 cases), 3.5% (16 cases), and 12% (50 cases), respectively. A multivariable analysis controlling for demographics, admitting department and prior morbidity showed an increased 1-year mortality in children with HA bacteremia (hazard ratio [HR] 4.1; 95% confidence interval [CI]: 1.3–12) and prior chronic disease (HR 3.4; 95% CI 1.2 to 9.0). MRSA was not independently associated with increased one-year mortality compared with MSSA: HR (95% CI: 1.4 [0.6–3.1]). Conclusions: Short-term pediatric mortality after SA bacteremia is low. HA-SA bacteremia has an increased long-term risk for mortality, particularly in children with chronic diseases. Our data suggest mortality was not increased for MRSA compared with MSSA bacteremia. The very low rate of CA-MRSA bacteremia justifies the current practice not to include glycopeptides in the empiric treatment of CA bacteremia in Israel. Abstract : Supplemental Digital Content is available in the text.